Cytotoxic lesions of the corpus callosum in children: Etiology, clinical and radiological features, and prognosis - YAPICI, ÖZGE (My University, 2021)
Objectives: Cytotoxic lesions of the corpus callosum (CLOCCs) are secondary lesions associated with entities like infection manifested by restricted diffusion on diffusion-weighted cranial magnetic resonance imaging. Our objectives are to evaluate the clinic-radiological spectrum of pediatric patients with cytotoxic lesions of the corpus callosum (CC).
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Nöroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Neurology; Health Sciences; KLİNİK NÖROLOJİ; Klinik Tıp; Klinik Tıp (MED); PEDİATRİ; CLINICAL NEUROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); PEDIATRICS; Pediatri; Pediatri, Perinatoloji ve Çocuk Sağlığı; Nöroloji (klinik); Yaşam Bilimleri; Pediatrics; Pediatrics, Perinatology and Child Health; Neurology (clinical); Life Sciences; Apparent life-threatening event (ALTE); COVID-19; Cytotoxic lesions of the corpus callosum (CLOCCs); Diffusion-weighted magnetic resonance imaging (MRI); Epilepsy; Mild encephalitis/encephalopathy with reversible splenial lesion (MERS); Reversible splenial lesion syndrome (RESLES); Saposin B deficiency; Urea cycle defect; REVERSIBLE SPLENIAL LESION; MILD ENCEPHALITIS/ENCEPHALOPATHY; ENCEPHALOPATHY